L'emploi des Latinos aux Etats-Unis : la deuxième génération dans la région métropolitaine de Chicago - Laurence Gervais-Linon (Les Cahiers ALHIM)
This article focuses on second generation Latinos in the Chicago Metropolitan Area where the income gap between minority groups and Anglos is still growing. Several metropolitan Chicago Latino areas showed underemployment. Between 1980 and 2000, the metropolitan Chicago job market suffered dramatic changes both in the importance of sectors and occupations and in the location of industries. The Latino areas have been particularly affected by these changes. The last two censuses in Chicago showed that the Latinos were the group most likely to be working poor, to have low educational levels and incomes under the average Chicago family income. Latinos have remained dependent of manufacturing jobs in spite of the shift to a service economy. Besides, the Latino community in Chicago is varied and not every family earns the same income. Last, the number of Latino workers has increased in the last years mainly amongst women. But the Hispanic patriarchal family structure is still the rule and tends to put a brake on Latinas' participation.